Abdominal fat depots associated with insulin resistance and metabolic syndrome risk factors in black African young adults. (December 2015) - De Lucia Rolfe, Emanuella; Ong, Ken; Sleigh, Alison; Dunger, David; Norris, Shane
Abstract Background Individuals of black African ethnicity tend to have less visceral adipose tissue (VAT) but more subcutaneous-abdominal adipose tissue (SCAT) than white Caucasians. However, it is unclear whether such distribution of abdominal fat is beneficial for metabolic disease risk in black individuals. Here we compared the associations between these specific abdominal fat depots, insulin sensitivity and metabolic syndrome risk. Methods A cross-sectional analysis of 76 black South African young adults (36 men; 40 women) aged 18–19 years participating in the Birth to Twenty Cohort Study had VAT and SCAT measured by MRI. The metabolic syndrome traits (blood pressure, lipid profile, fasting glucose and insulin) were measured and the values were combined into a metabolic syndrome risk score. Fasting glucose and insulin were used to derive the HOMA-index of insulin resistance (HOMA-IR). Results Compared to men, women had greater VAT (mean: 16.6 vs. 12.5 cm2 ) and SCAT (median 164.0 vs. 59.9 cm2 ). In men, SCAT (r = 0.50) was more strongly correlated to the metabolic syndrome score (MetS) than was VAT (r = 0.23), and was associated with both MetS (P = 0.001) and HOMA-IR (P = 0.001) after adjustment for VAT and total fat mass. In women, both abdominal fat compartments showed comparable positive correlations with MetS (r = 0.26 to 0.31), although these trends were weaker than in men. Conclusions In young black South African adults, SCAT appears to be more relevant than VAT to metabolic syndrome traits.